Communication between cultures - Samovar, Larry A. (Wadsworth / Cengage Learning, 2013)
This bestselling intercultural communication text gives readers an understanding and appreciation of different cultures and helps them develop practical skills for improving their communication with people from other cultures. COMMUNICATION BETWEEN CULTURES is renowned for being the only text on the market to consistently emphasize religion and history as key variables in intercultural communication. Packed with the latest research and filled with numerous compelling examples that force readers to examine their own assumptions and cultural biases, this book helps students understand the subtle and profound ways culture affects communication. The book is divided into four interrelated parts: Part I introduces the study of communication and culture; Part II focuses on the ability of culture to shape and modify our view of reality; Part III puts the theory of intercultural communication into practice; and Part IV converts knowledge into action.